The Effectiveness of BPHTB Online in The Effort of Preventing Tax Funds and Regional Revenues in Asahan District - Rahmat Lubis; Bastari; Utary Maharany Barus; Maria (IHSA Institute, 2022)
This research is descriptive in nature. a method for describing an ongoing state or situation, the purpose of which is to produce information about research subjects to examine ideal problems. The data source of this research is secondary data. Documented data was used as a data collection tool for this study, supported by candid interviews with tax officers in Asahan District and notaries working at Batu Bara. Based on the survey results, it turns out that online verification of the Asahan District BPHTB (Regional Financial and Asset Management Agency) cannot actually be carried out because the levy is not regulated regionally. from BPHTB. The constraints faced by the Regional Office for Finance and Asset Management in Asahan Regency lie in the era of e-government. - There are still taxpayers at BPHTB who do not understand how to use e-BPHTB, so that taxpayers find it difficult to enter information about BPHTB online, as well as incomplete local tax information and communication to the public. Information is an important source in policy implementation, the availability of sufficient information to support good policy implementation, information on BPHTB tax policy implementation.